Integrative Radiogenomics Approach for Risk Assessment of Postoperative and Adjuvant Chemotherapy Benefits for Gastric Cancer Patients - Jin, Yin; Xu, Yilun; Li, Yanyan; Chen, Renpin; Cai, Weiyang (Frontiers in Oncology, 2021)
GC is a typical heterogeneous malignant tumor, whose insensitivity to chemotherapy is a common cause of tumor recurrence and metastasis. There is no doubt regarding the effectiveness of adjuvant chemotherapy (ACT) for GC, but the population for whom is indicated and the selection of specific options remains the focus of current research. The conventional TNM prediction focuses on cancer cells to predict prognosis, while they do not provide sufficient prediction. Enhanced computed tomography (CT) scanning is a validated tool that assesses the involvement careful identification of the tumor, lymph node involvement, and metastatic spread. Using radiomics approach, we selected least absolute shrinkage and selection operator (LASSO) Cox regression model to build a radiomics signature for predicting the overall survival (OS) and disease-free survival (DFS) of patients with complete postoperative gastric cancer patients, and further identifying candidates benefit from ACT. The radimoic trait-associated genes captured clinically relevant molecular pathways and potential chemotherapeutic drug metabolism. Our results of precise surrogates using radiogenomics can lead to additional benefit from adjuvant chemotherapy or survival prediction in postoperative gastric cancer patients.